Antibacterial Activity of Pluchea indica Leaf Extract was Increased After Being Fermented with Saccharomyces cerevisiae and Added with its Cell-Free Supernatant - Rismawati, Ria; Jatmiko, Yoga Dwi; Widyarti, Sri (Biotropika: Journal of Tropical Biology, 2022)
Multi Drug Resistance (MDR) is a global health problem that endangers public health and can lead to death. Therefore, novel antibacterial agents are required derived from medicinal plants, one of them is beluntas (Pluchea indica) which has high potential as an antibacterial. Fermentation or addition of cell-free supernatant of Saccharomyces cerevisiae is thought to increase the antibacterial content of an herb. This study aimed to evaluate the effect of fermentation and the addition of Cell-Free Supernatant (CFS) of S. cerevisiae to enhance antibacterial activity of P. indica leaf extract. Fresh and dried leaves of beluntas were used in this study. The dried leaves in the form of powder was boiled at 100oC for 45 minutes. Fresh leaves were homogenized by blending. The extract of P. indica was used for fermentation and addition of CFS of S. cerevisiae. CFS as much as 60 mL dan fermentation with cell density of 7.53x105 CFU/mL with 100 mL of P. indica leaf extract were centrifuged at 10,000 rpm for 20 minutes. The antibacterial test method used was the Kirby-Bauer method against Escherichia coli and Staphylococcus aureus. The results showed an increase in antibacterial activity as indicated by the increasing diameter of the inhibition zone either by fermentation or addition of CFS with inhibition zone diameter was 3.85 – 4.81 mm against E. coli and 4.63 – 5.12 mm against S. aureus. The fermented P. indica and addition of CFS was shown to be potentially developed as antibacterial agents. Keywords: Antibacterial, CFS, fermentation, Pluchea indica, Saccharomyces cerevisiae